A March to Shape Optical Artificial Olfactory System toward Ultrasensitive Detection of Improvised Explosives. Issue 7 (25th February 2022) - Zhang, Tianshi; Hu, Xiaoyun; Zu, Baiyi; Dou, Xincun
Abstract : Improvised explosives (IEs) have been frequently used in explosion‐based terrorist attacks, and have aroused widespread concerns from governments to academic societies. Due to the fact that IEs mostly exist as solids, there is a pressing demand for sensors to adapt to acquire the information from the solid state. Chemical sensors usually comprise with probes designed based on the chemical properties of the analytes, and generate signals through specific chemical interactions, which would not be affected by the state of the target substance. Colorimetry and fluorescence, known for their intuitionistic (recognizable by human eyes), portable (independent of large‐scale analytical equipment), highly specific, sensitive, and environmental interference‐free characteristics, are commonly adopted optical chemical detection methods in materials analysis and environmental monitoring. Based on this, the exploration of optical artificial olfactory system, which mimics the working principle of natural olfactory system and acquires sensing signal by optical methods, has emerged to be a promising tool for IEs detection. Here, the basic working principle and the necessary components of optical artificial olfactory system are recommended, including probe molecule, array composition, pattern recognition and device construction. The potential development direction employing molecular recognition of IEs, generation, and acquisition methodology of optical signals are also prospected. Abstract : Improvised explosives (IEs) detection using probe, substrate, array, and recognition components are currently studied by many researchers. To meet the needs of real‐time monitoring, optical artificial olfactory system aroused by biomimic design can grant new functions. It is with great potential to be detector of IEs with various chemical characterizations and can provide progress in the field of chemical sensors.